Diagnosis and management of low-flow, low-gradient aortic stenosis. (March 2020) - Salemi, Arash; Hameed, Irbaz; Khan, Faiza M.; Gaudino, Mario
Abstract : Purpose of review: The severity of low-flow, low-gradient aortic stenosis cases continue to be misunderstood because of challenging diagnosis, and treatment remains complex. We discuss current diagnostic and treatment modalities for low-flow, low-gradient aortic stenosis. Recent findings: This article summarizes current guidelines and best practices for the management of low-flow, low-gradient aortic stenosis. Summary: Low-flow, low-gradient aortic stenosis is a difficult entity to diagnose and treat. Various diagnostic modalities are needed to accurately determine the severity of aortic stenosis and potential treatment benefit. True-severe classical and paradoxical low-flow, low-gradient aortic stenosis can be distinguished from pseudo-severe aortic stenosis by dobutamine stress echocardiography and/or multidetector computed tomography. Once the distinction is made, aortic valve replacement results in better outcomes compared with conservative management. Although both surgical and transcatheter aortic valve replacement result in adequate outcomes, the decision between the two treatment strategies is based on patient characteristics, valve morphology, and other risk factors.